Influence of immediate release tablet formulation on dissolution profile of paracetamol - Todorović Nemanja B.; Goločorbin-Kon Svetlana S.; Kermeci Kristina N.; Jovičić-Bata Jelena N.; Pavlović Nebojša M.; Milijašević Boris Ž.; Lalić-Popović Mladena N. (Srpsko lekarsko drustvo, 2018)
Introduction: Paracetamol is analgesic and antipyretic, which is usually in the form of an immediate release tablet formulations. Therapeutic effects in terms of the speed and intensity of the analgesic effect is dependent on speed of liberation from formulation. Aim: The aim of this work was to determine and compare dissolution profiles of 4 paracetamol immediate release tablet formulations and to determine influence of excipients on kinetic of paracetamol dissolution. Materials and Methods: Dissolution profiles of paracetamol tablets were determined using method with paddles and phosphate buffer pH 6.8 as a medium. Release of paracetamol was followed 60 minutes (using 6 time points). Concentration of paracetamol was measured using UV/Vis spectrophotometric method (243 nm). Dissolution profiles were compared using model-independent method (difference factor and similarity factor), statistic method (ANOVA-based method and pair Student's T-test, p<0.05) and model dependent methods (to determinate the release kinetics of paracetamol). Results: All formulations in the first 45 minutes liberated more than 85 % of the labled content. Formulation D, which contained superdesintegrator, released 90% of the content in the first 5 minutes. Though based on values of difference and similarity factors formulations are, not significantly different, ANOVA-based method showed that formulation A and B, B and C, as well as formulation B and D do statistically differ in all 6 time points, meaning they have parallel profiles. The release of paracetamol from formulations A and D is best described by the first order kinetic model, while the release of formulations B and C by the logistic model. Conclusions: The release kinetic of paracetamol is mostly influenced by the type of superdisintegrants and lubricants. Formulation with superdisintegrant technology OptiZorb® demonstrated fastes release rate and thus it is expected to produce the fastest pharmacodynamic effect. .